2011
DOI: 10.5001/omj.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites among Patients of Al-Noor Specialist Hospital, Makkah, Saudi Arabia

Abstract: The notable finding from this study is the high prevalence of E. histolytica. Overall, parasitic infections were more prevalent in patients under five years of age and in non-Saudi nationals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
25
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 10 publications
11
25
9
Order By: Relevance
“…In contrast, the present finding was higher than results from different localities of Ethiopia [2, 24, 25] and other parts of the world; Kashmir (18.02%) [26] and Saudi Arabia 6.2% [27]. This might be attributable to differences in environmental and personal hygiene, source of households’ water supply, and habit of walking bare-footed.…”
Section: Discussioncontrasting
confidence: 91%
“…In contrast, the present finding was higher than results from different localities of Ethiopia [2, 24, 25] and other parts of the world; Kashmir (18.02%) [26] and Saudi Arabia 6.2% [27]. This might be attributable to differences in environmental and personal hygiene, source of households’ water supply, and habit of walking bare-footed.…”
Section: Discussioncontrasting
confidence: 91%
“…13 The present retrospective study revealed that the overall prevalence of intestinal parasitic infestation in our set up is 8.17%.This finding is consistent with the findings of the studies done in Saudi Arabia, Ethiopia and Iran. [14][15][16] Inconsistent with this finding, there are several studies conducted round the globe which has shown higher prevalence of parasitic infestation. For example, in a study in rural southern India, the overall period prevalence of intestinal parasites was 97.4% per month 17 and in another study in Sierra Leone showed a prevalence rate of 73.5%.…”
Section: Discussionmentioning
confidence: 61%
“…The high frequency of intestinal parasites in a population of a region indicates low socioeconomic development or conditions, poor medical care, occupational exposure and low standard of hygiene (31) . Therefore, the aim of this study was to assess the prevalence of helminthic infection and its effect on the health status of primary school children.The present study showed that there was higher prevalence of parasitic infection among the studied school children in which, more than three quarter of the studied school children (79%) was infected by intestinal parasite (figure 1), and all of the studied school children had poor knowledge about intestinal parasitic infection (table 3).…”
Section: Discussionmentioning
confidence: 99%